Penerapan Teknologi Mesin Pencacah Rumput Untuk Kemandirian Pakan Di Kelompok Ternak Ngudi Makmur - Badrawada, I Gusti Gde; Yudha, Venditias (Society : Jurnal Pengabdian Masyarakat, 2023)
Most of the livelihoods of residents in Klegen Hamlet, Trimulyo, Sleman District are mostly cattle breeders. Feeding with fresh grass needs to pay attention to the dimensions of the grass so that it is easily digested by livestock. This service activity focuses on the application of appropriate technology in the form of a grass chopper that is applied to the Makmur cattle group. The method of implementing the program is by dissemination and counseling on the operation and maintenance of machines. The grass chopper has a simple design that makes it easy to operate and maintain. The application of a grass chopper in the prosperous Ngudi livestock group can increase productivity in chopping grass by up to 30 times compared to the manual chopping process.